Hydrated materials : applications in biomedicine and the environment - Nakanishi, Yoshitaka (Pan Stanford Publishing, 2015)
Water covers more than 70% of the earth's surface and is an essential and major component of all living matter. However, artificially hydrated materials, including hydrophilic materials, are far fewer than one might expect. Currently, these materials are in a state of development for applications in fields such as biomedicine, environmental engineering, and industrial engineering. So what do artificially hydrated materials hold for the future? This book is a great introduction to hydrated materials, presenting academic and practical content that gives a feel of theoretical as well as real-worl.